Cervus and cucumis peptides ameliorates bone erosion in experimental arthritis by inhibiting osteoclastogenesis - Ze-Min Lin; Yu-Ting Liu; Yan-Sheng Xu; Xiao-Qian Yang; Feng-Hua Zhu; Wei Tang; Shi-Jun He; Jian-Ping Zuo (Lupus Science and Medicine, 2019)
Objective Rheumatoid arthritis is an autoimmune disease characterised by inflammation and bone loss, leading to joint destruction and deformity. The cervus and cucumis polypeptide (CCP) injection, one of the traditional Chinese medicine injections combined extracts from deer horn and sweet melon seeds, is widely used to treat arthritis and bone fracture in China. The present study investigated the therapeutic efficacy and mechanism of CCP on pathological immune cells and bone homoeostasis in rodent experimental arthritis.Methods The effects of CCP (4 mg/kg and 2 mg/kg) on clinical arthritis symptoms, bone erosion, proinflammatory cytokines and pathological immune cells induced by complete Freund’s adjuvant was evaluated in male Sprague-Dawley rats. The impacts of CCP (2 mg/kg) on joint erythema and swelling, production of pathogenic antibodies and the proportion of inflammatory cells were assessed in collagen-induced arthritis (CIA) in DBA/1J mice. Regulation of osteoclastogenesis by CCP was observed in the murine macrophage-like RAW264.7 cells treated with receptor activator of nuclear factor-κB ligand (RANKL) and macrophage colony-stimulating factor (M-CSF).Results CCP administration significantly prevented disease progression in both adjuvant-induced arthritis (AIA) rats and CIA mice. The therapeutic benefits were accompanied by reduction of paw oedema, reversed bone destruction, decreased pathological changes and osteoclast numbers in joints in AIA rats, as well as attenuated clinical manifestation and autoantibodies production in CIA mice. Meanwhile, in vitro supplemented of CCP concentration dependently inhibited RANKL/M-CSF-induced osteoclast differentiation, without showing cytotoxicity in RAW264.7 cells. Further, the presence of CCP dampened the augmented downstream signalling transduction as well as activation of osteoclast-specific genes and transcription factors induced by RANKL/M-CSF in RAW264.7 cells.Conclusion Our study suggested that the therapeutic effects of CCP in experimental arthritis could be attributed to its intervention on RANKL-induced osteoclastogenesis signalling pathway in osteoclast precursor cells.